Sexual Orientation Disparities in Cancer-Related Risk Behaviors of Tobacco, Alcohol, Sexual Behaviors, and Diet and Physical Activity: Pooled Youth Risk Behavior Surveys - Rosario, Margaret (American Public Health Association, 2014)
Objectives. We examined sexual orientation disparities in cancer-related risk behaviors among adolescents. Methods. We pooled data from the 2005 and 2007 Youth Risk Behavior Surveys. We classified youths with any same-sex orientation as sexual minority and the remainder as heterosexual. We compared the groups on risk behaviors and stratified by gender, age (< 15 years and > 14 years), and race/ethnicity. Results. Sexual minorities (7.6% of the sample) reported more risk behaviors than heterosexuals for all 12 behaviors (mean = 5.3 vs 3.8; P < .001) and for each risk behavior: odds ratios (ORs) ranged from 1.3 (95% confidence interval [CI] = 1.2, 1.4) to 4.0 (95% CI = 3.6, 4.7), except for a diet low in fruit and vegetables (OR = 0.7; 95% CI = 0.5, 0.8). We found sexual orientation disparities in analyses by gender, followed by age, and then race/ethnicity; they persisted in analyses by gender, age, and race/ethnicity, although findings were nuanced. Conclusions. Data on cancer risk, morbidity, and mortality by sexual orientation are needed to track the potential but unknown burden of cancer among sexual minorities.